An Expert System for Estimating Cost and Analysis of Air Pollution Control - Ekechukwu, Boniface (1998)
Expert System for Estimating Cost and Analysis of Air Pollution Control was developed using CLIPS. The developed Expert Systems facilitate decision making involving selection of the best available technology as control measure. It was discovered that at equilibrium, total cost of reduction is equal to total cost of damages. It was further found that change in quantity of Air pollution is positive. This shows direct relationship. Total excess damage is directly proportional to total cost of reduction. When excess damage is increasing the total cost of reduction is increasing as well. In the same way, when total cost of reduction is decreasing, the excess damage is decreasing as well. The total cost function is dependent on the quantity of emission of the form: TC=f(Q) where TC is the total cost and Q is the quantity of emission. Hence TC=QxP where P is the unit price. There was also a break-through in the estimation of Welfare loss due to excess pollution. The relationship between quantity of excess pollution and Welfare loss due to excess pollution was derived. This devoted and faithful research has further developed Emission Elasticity.